Affective States and the Notion of Happiness: A Preliminary Analysis - Heinz Welsch; Jan Kühling (University of Oldenburg, Department of Economics, 2014)
Large-scale social surveys typically elicit levels of happiness and/or life satisfaction. This paper studies how such reports of happiness and life satisfaction are related to measures of positive affect (PA) and negative affect (NA). Major findings are the following: (1) PA and NA levels jointly predict happiness better than they predict life satisfaction. (2) PA levels predict happiness better than do NA levels. (3) NA levels predict life satisfaction better than do PA levels. (4) The PA items that predict happiness include those that predict life satisfaction (but not vice versa). (5) The NA items that predict happiness are distinct from those that predict life satisfaction. The study contributes to the literature by characterizing reported happiness and life satisfaction in terms of the specific positive and negative affects involved, thus clarifying their respective affective state content. Finding (4) is consistent with the mediator model of affective and cognitive well-being, according to which people in part directly rely on the affective component to judge life satisfaction. Our results are robust to several methodological strategies, but preliminary with regard to the small sample size (N = 144).
Keywords: 330; happiness; life satisfaction; positive affect; negative affect; social welfare